International comparison of cosmetic outcomes of breast conserving surgery and radiation therapy for women with ductal carcinoma in situ of the breast. (January 2020) - Olivotto, Ivo A.; Link, Emma; Phillips, Claire; Whelan, Timothy J.; Bryant, Guy; Kunkler, Ian H.; Westenberg, A. Helen; Purohit, Kash; Ahern, Verity; Graham, Peter H.; Akra, Mohamed; McArdle, Orla; et al.
Highlights: Cosmetic outcomes of BCS for DCIS were independent of treating centre geography. Conventional and hypofractionated WBI achieved similar 3-year cosmesis. Tumour bed boost (16 Gy in 8 fractions) doubled the risk of cosmetic deterioration. The adverse impact of a tumour bed boost was independent of WBI fractionation. Abstract: Purpose: To assess the cosmetic impact of breast conserving surgery (BCS), whole breast irradiation (WBI) fractionation and tumour bed boost (TBB) use in a phase III trial for women with ductal carcinoma in situ (DCIS) of the breast. Materials and methods: Baseline and 3-year cosmesis were assessed using the European Organization for Research and Treatment of Cancer (EORTC) Cosmetic Rating System and digital images in a randomised trial of non-low risk DCIS treated with postoperative WBI +/− TBB. Baseline cosmesis was assessed for four geographic clusters of treating centres. Cosmetic failure was a global score of fair or poor. Cosmetic deterioration was a score change from excellent or good at baseline to fair or poor at three years. Odds ratios for cosmetic deterioration by WBI dose-fractionation and TBB use were calculated for both scoring systems. Results: 1608 women were enrolled from 11 countries between 2007 and 2014. 85–90% had excellent or good baseline cosmesis independent of geography or assessment method. TBB (16 Gy in 8 fractions) was associated with a >2-fold risk of cosmetic deterioration ( p  < 0.001). Hypofractionated WBI (42.5 Gy in 16 fractions) achieved statistically similar 3-year cosmesis compared to conventional WBI (50 Gy in 25 fractions) ( p  ≥ 0.18). The adverse impact of a TBB was not significantly associated with WBI fractionation (interaction p  ≥ 0.30). Conclusions: Cosmetic failure from BCS was similar across international jurisdictions. A TBB of 16 Gy increased the rate of cosmetic deterioration. Hypofractionated WBI achieved similar 3-year cosmesis as conventional WBI in women treated with BCS for DCIS.